Posterior vertebrodesis and Ponte osteotomies in surgical treatment of adolescent idiopathic scoliosis type Lenke 1-4 - Adelin Ivanov (Journal of the Bulgarian Orthopaedics and Trauma Association)
The purpose of the study is to present the results of the application of posterior vertebrodesis with Ponte osteotomies (PO) in the operative treatment of adolescent idiopathic scoliosis /AIS/, Lenke 1-4. The study encompasses patients with more than 60 degrees Cobb angle rigid deformities in the frontal plane with correction below 40% percents in the bending tests. Patients with both hyperkyphosis reported in the T5-T12 segment and marked hypokyphosis in the same area of the thoracic zone were also included in the study.